2014
DOI: 10.3389/fphar.2013.00173
|View full text |Cite
|
Sign up to set email alerts
|

The epithelium in idiopathic pulmonary fibrosis: breaking the barrier

Abstract: Idiopathic pulmonary fibrosis is a progressive disease of unknown etiology characterized by a dysregulated wound healing response that leads to fatal accumulation of fibroblasts and extracellular matrix (ECM) in the lung, which compromises tissue architecture and lung function capacity. Injury to type II alveolar epithelial cells is thought to be the key event for the initiation of the disease, and so far both genetic factors, such as mutations in telomerase and MUC5B genes as well as environmental components,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
179
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(195 citation statements)
references
References 108 publications
1
179
0
1
Order By: Relevance
“…1 Although the etiology and pathogenesis of IPF still remains elusive, it is now suggested that epithelial cell injury-induced abnormal wound healing process has a critical role in the initiation and progression of IPF. 2 Lung fibroblasts are the major effector cells involved in the dysregulated wound healing process, because overactivation and migration of them and their transition into myofibroblasts mainly contribute to the fibrous intercellular matrix production. 3 One of the aberrant features of fibroblasts is that they produce excessive autocrine profibrotic mediators, including connective tissue growth factor (CTGF, CCN2).…”
mentioning
confidence: 99%
“…1 Although the etiology and pathogenesis of IPF still remains elusive, it is now suggested that epithelial cell injury-induced abnormal wound healing process has a critical role in the initiation and progression of IPF. 2 Lung fibroblasts are the major effector cells involved in the dysregulated wound healing process, because overactivation and migration of them and their transition into myofibroblasts mainly contribute to the fibrous intercellular matrix production. 3 One of the aberrant features of fibroblasts is that they produce excessive autocrine profibrotic mediators, including connective tissue growth factor (CTGF, CCN2).…”
mentioning
confidence: 99%
“…Proper epithelial-mesenchymal cell interactions are critical for maintaining normal tissue function, as damage to the lung epithelium upon exposure to agents such as asbestos, silica, or bleomycin induces morphological changes that disrupt the homeostasis between the epithelium and the underlying mesenchymal cells. 43,44 These changes to the epithelium may lead to EMT and/or the recruitment, activation, and proliferation of lung fibroblasts that leads to subsequent ECM accumulation. In our model, we observed marked STAT3 activation and SMAD1/5/8 signaling suppression in epithelial cells in vivo upon OSM overexpression and further work is required to determine whether OSM can induce EMT through a STAT3/SMAD1 signaling dichotomy.…”
Section: Discussionmentioning
confidence: 99%
“…While pulmonary inflammation and loss of lung architecture in IPF involve interactions among multiple cell types, recent studies provide increasing support for the concept that injury to the respiratory epithelium plays an important role in IPF pathogenesis (4,5). Loss of normal alveolar architecture in IPF is accompanied by fibrotic remodeling, loss of AT1 and AT2 cells, and the presence of atypical epithelial cells expressing differentiated cell markers characteristic of proximal airways and submucosal glands (e.g., basal cell and goblet cell markers) in the normal lung (6,7).…”
Section: Introductionmentioning
confidence: 99%